2013
DOI: 10.1007/s13762-013-0198-z
|View full text |Cite|
|
Sign up to set email alerts
|

Biosorption of Cu(II) and Pb(II) from aqueous solutions by chemically modified spent coffee grains

Abstract: In this research, spent coffee grains were modified with citric acid solutions (0.1 and 0.6 M) to increase the quantity of carboxylic groups improving its metal adsorption capacity. Added functional groups on modified and non-modified spent coffee grains were identified and quantified by attenuated total reflection Fourier transform infrared analyses and potentiometric titrations, respectively. These adsorbents were used for the removal of lead (II) and copper (II) from aqueous solutions at 30°C and different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…Many industrial activities such as mining, electroplating and smelting resulted in the release of heavy metal ions into water (Cerino-Cordova et al, 2013;Sarada et al, 2014). Lead (Pb) has been recently gained an increasing attention owing to its high toxicity to human body (Gundogdu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many industrial activities such as mining, electroplating and smelting resulted in the release of heavy metal ions into water (Cerino-Cordova et al, 2013;Sarada et al, 2014). Lead (Pb) has been recently gained an increasing attention owing to its high toxicity to human body (Gundogdu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Dubinin-Radushkevich (D-R) isotherm is more general because it does not assume a homogenous surface or constant sorption potential and was applied to estimate the porosity apparent free energy and the characteristics of sorption (Cerino-Cordova et al 2013 …”
Section: Adsorption Isothermmentioning
confidence: 99%
“…The saturation adsorption capacity q m obtained using D-R isotherm model for adsorption of DBP onto PLAC is 124.31 mg/g, which is close to that obtained from Langmuir isotherm model (133.33 mg/g). The mean free energy of adsorption (E), defined as the free energy change when 1 mol of ion is transferred from infinity in solution to the surface of the sorbent, was calculated from the B value using the following relation (Cerino-Cordova et al 2013):…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggshell membranes and orange peels are abundantly available with the eggshell membranes being available throughout the year whilst the orange peels are seasonal, yet the output when in season is too high to ignore. Latest studies showed that dehydrated aquatic plants (Deng et al 2013) and spent coffee grains (Cerino-Córdova et al 2013) could also be used as lowcost adsorbents. Utilising such materials is desirable for providing cheap techniques suitable for the removal of contaminants present in water (Abdel et al 2011;Love and Thatcher 1953).…”
Section: Introductionmentioning
confidence: 99%